Fulfillment of the Guarantee of Voting Rights for Voters with Disabilities in Metro City under Law Number 8 of 2016: Pemenuhan Jaminan Hak Pilih Pemilih Penyandang Disabilitas di Kota Metro Menurut Undang-Undang Nomor 8 Tahun 2016 - Betha Rahmasari; Nurul Amalia (Lex Renaissance, 2023)
The emphasis is placed on the importance of protecting human rights, including the political rights of people with disabilities, in the context of the Rule of Law to achieve well-being and justice. Challenges in implementing general elections for people with disabilities and the significance of their presence in the political system. The implementation of Article 5 of Law Number 8 of 2016 regarding people with disabilities as voters in general elections in Metro city. The determination and barriers faced by people with disabilities in the conduct of elections in Metro city. This research aims to understand the implementation of Article 5 of Law Number 8 of 2016 concerning the voting rights of people with disabilities in general elections and to find out how to determine and overcome barriers faced by people with disabilities in the conduct of general elections. This research uses a type of empirical juridical research that examines and analyzes facts obtained from research results and field observations. Fulfilling the rights of people with disabilities through laws increases participation in general elections, but barriers need to be overcome, and accessibility and disability-friendly electoral movements are taken into consideration. The role of election organizers needs to be enhanced, and cooperation with the disability community is required.Keywords: Disabilities, Guarantee, General Elections AbstrakPenekanan diberikan pada pentingnya perlindungan hak asasi manusia, termasuk hak politik penyandang disabilitas, dalam konteks Negara Hukum untuk mencapai kesejahteraan dan keadilan. Kendala dalam pelaksanaan pemilihan umum bagi penyandang disabilitas dan pentingnya kehadiran mereka dalam sistem politik. Implementasi Pasal 5 Undang-Undang Nomor 8 Tahun 2016 terhadap penyandang disabilitas sebagai hak pilih dalam pemilihan umum di kota Metro. Penetapan dan hambatan penyandang disabilitas dalam penyelenggara pemilu di kota Metro. Penelitian ini bertujuan untuk memahami pelaksanaan Pasal 5 Undang-Undang Nomor 8 Tahun 2016 terhadap hak pilih penyandang disabilitas dalam pemilihan umum dan mengetahui cara menetapkan serta mengatasi hambatan penyandang disabilitas dalam penyelenggaraan pemilihan umum. penelitian ini menggunakan jenis penelitian yuridis empiris yang mengkaji dan menganalisa fakta-fakta yang diperoleh dari hasil penelitian dan observasi di lapangan. Pemenuhi hak-hak penyandang disabilitas dengan undang-undang, partisipasi pemilihan umum meningkat, tetapi hambatan perlu diatasi, aksesibilitas dan gerakan pemilu ramah disabilitas diperhatikan. Peran penyelenggara pemilihan umum perlu ditingkatkan, dan kerjasama dengan komunitas disabilitas diperlukan.Kata Kunci: Disabilitas, Jaminan, Pemilihan Umum